Macaques as model hosts for studies of HIV-1 infection - Misra, Anisha; Thippeshappa, Rajesh; Kimata, Jason T. (Frontiers in Microbiology, 2013)
Increasing evidence indicates that the host range of primate lentiviruses is in part determined by their ability to counteract innate restriction factors that are effectors of the type 1 interferon (IFN-1) response. For HIV-1, in vitro experiments have shown that its tropism may be narrow and limited to humans and chimpanzees because its replication in other nonhuman primate species is hindered by factors such as TRIM5α, APOBEC3G, and Tetherin. Based on these data, it has been hypothesized that primate lentiviruses will infect and replicate in a new species if they are able to counteract and evade suppression by the IFN-1 response. Several studies have tested whether engineering HIV-1 recombinants with minimal amounts of SIV sequences would enable replication in CD4+ T-cells of non-natural hosts such as Asian macaques and proposed that infection of these macaque species could be used to study transmission and pathogenesis. Indeed, infection of macaques with these viruses revealed that Vif-mediated counteraction of APOBEC3G function is central to cross-species tropism but that other IFN-induced factors may also play important roles in controlling replication. Further studies of these macaque models of infection with HIV-1 derivatives could provide valuable insights into the interaction of lentiviruses and the innate immune response and how lentiviruses adapt and cause disease.